Cavitation Induced by Janus-Like Mesoporous Silicon Nanoparticles Enhances Ultrasound Hyperthermia - Sviridov, Andrey; Tamarov, Konstantin; Fesenko, Ivan; Xu, Wujun; Andreev, Valery; Timoshenko, Victor; Lehto, Vesa-Pekka (Frontiers in Chemistry, 2019)
The presence of nanoparticles lowers the levels of ultrasound (US) intensity needed to achieve the therapeutic effect and improves the contrast between healthy and pathological tissues. Here, we evaluate the role of two main mechanisms that contribute to the US-induced heating of aqueous suspensions of biodegradable nanoparticles (NPs) of mesoporous silicon prepared by electrochemical etching of heavily boron-doped crystalline silicon wafers in a hydrofluoric acid solution. The first mechanism is associated with an increase of the attenuation of US in the presence of NPs due to additional scattering and viscous dissipation, which was numerically simulated and compared to the experimental data. The second mechanism is caused by acoustic cavitation leading to intense bubble collapse and energy release in the vicinity of NPs. This effect is found to be pronounced for as-called Janus NPs produced via a nano-stopper technique, which allow us to prepare mesoporous NPs with hydrophobic inner pore walls and hydrophilic external surface. Such Janus-like NPs trap air inside the pores when dispersed in water. The precise measurement of the heating dynamics in situ enabled us to detect the excessive heat production by Janus-like NPs over their completely hydrophilic counterparts. The excessive heat is attributed to the high intensity cavitation in the suspension of Janus-like NPs. The present work elicits the potential of specifically designed Janus-like mesoporous silicon NPs in the field of nanotheranostics based on ultrasound radiation.